A clinical audit on the quality of care and the outcome of patients with pregnancy induced hypertension within a primary-secondary care pathway: the Wesfleur-New Somerset Hospital Axis, Cape Town, South Africa. - Sobamowo, Theophilus Oluwadayo (Department of Public Health and Family Medicine, 2021)
Background: Pregnancy Induced Hypertension (PIH) and its complications contribute to a significant burden of disease both in developed and developing countries of the world. Unfortunately, PIH has no cure, the delivery of the baby and the placenta is required. Early detection of pregnancy induced hypertension and close monitoring remains the key to achieving a favourable outcome. This study aimed to determine the quality of care given to women diagnosed with Pregnancy Induced Hypertension (PIH) within a care pathway spanning peri-urban primary and urban secondary level facilities. Methods: This was a retrospective clinical audit of medical records of patients diagnosed with PIH. It was conducted in the Wesfleur -New Somerset Hospital drainage area, using a locally validated data extraction tool, based on the South African Maternal Care Guidelines. The data were analyzed using descriptive methods to report on the frequencies and proportions of the variables, and analyzed to report on statistical significance of correlations. Results: The prevalence rate of pregnancy induced hypertension in this study was 12%. The overall pregnancy induced hypertension complication prevalence in the study for mothers was 7.7%, and that of babies was 30.7%. Facilities generally performed well according to the audit indicators detailing structures and processes that should be followed, as outlined by the standard guidelines used. Two process indicators were correlated with adverse outcomes: 66.1% of patients were appropriately referred, resulting in statistically better foetal outcomes (p = 0.059); and those who booked early in the pregnancy had less PIH-induced complications than those who booked late (p = 0.012) Conclusion: This study followed a standardized audit methodology and found that the quality of care in this peri-urban area is of a good standard and identified areas for quality improvement and further enquiry to ensure continual improvement in maternal and fetal outcomes.